Engage in Exploration: Pathology Gross Laboratory in the COVID-Era - Ronald J. Bryant MD; Rebecca Wilcox MD; Bei Zhang MD, PhD, MLS (ASCP) (Elsevier, 2021)
The outbreak of Covid-19 has changed education, including the mechanism of delivery of gross pathology laboratories. Herein, we describe how we revised our preclinical gross pathology lab to a flipped model to fit with COVID-19 regulations. A series of short, session objective-driven videos are made available online. Students are expected to watch the videos before coming to the hands-on lab. Groups of 2 students enter the gross lab on a timed basis and rotate through a series of stations. At each station, students examine gross pathology specimens while answering questions designed to apply the clinical correlation of pathophysiology and heighten observational skills. One or 2 pathologists are available throughout the lab session to address the questions from the students. The design of this laboratory exercise maintains appropriate distancing and hygiene in the time of COVID-19. The laboratory rooms are mapped to set up an appropriate number of timed stations. Flow-through of the rooms is unidirectional. Comparing with the traditional show-and-tell of teaching gross pathology, the renovated flipped model is genuinely student-centered and focuses on active learning. Holding the specimen in their hands, students learn from discovery as they are completely engaged by exploring the specimen and deriving answers themselves. The flipped learning gross pathology method has been very well received and evaluated highly by both faculty and students.